2018
DOI: 10.1002/app.46456
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic rheological behavior of poly(ether ketone ketone) from solid state to melt state

Abstract: High performance thermoplastic poly(ether ketone ketone) (PEKK) polymers with various meta phenyl links ratio were investigated by dynamical mechanical analysis. Analyses were carried out in a wide range of temperature from solid state (torsion rectangular mode) to the melt state (torsion parallel plates mode) as function of thermal history and environmental conditions. In the solid state, this study was focused on the secondary relaxations in the vitreous state. A complementary investigation conducted with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…At low temperature, the broad peak at about À90 C is labelled g relaxation. It has been associated in the literature with dipolar entities which can interact with water like ketone groups present on the main chain [34,35]. Literature also highlights another secondary relaxation named b, located at around À60 C, associated with the oscillation of phenyl groups around their axis.…”
Section: Evidence Of Cross-linking Through Absorption Testsmentioning
confidence: 98%
“…At low temperature, the broad peak at about À90 C is labelled g relaxation. It has been associated in the literature with dipolar entities which can interact with water like ketone groups present on the main chain [34,35]. Literature also highlights another secondary relaxation named b, located at around À60 C, associated with the oscillation of phenyl groups around their axis.…”
Section: Evidence Of Cross-linking Through Absorption Testsmentioning
confidence: 98%
“…At low temperature, the γ relaxation is associated with localised mobility of polar groups. Studies have concluded that this relaxation is allowed by the presence of water molecules absorbed in the polymer [32,33]. At higher temperature, the relaxation named α is associated with the mechanical manifestation of the glass transition.…”
Section: Cross-linking Density Influence On Absorption Behaviourmentioning
confidence: 99%
“…25,26,27,28 The consequence of these chemical reactions is a modification of the molecular weight, 26 but also modifications of the physical and mechanical properties like the crystallization behavior, melting and glass transition temperatures as well as modulus. 29,30,31,32 In particular, the crosslinking process results in a rapid increase of the polymer viscosity, 30,32,33 which has a detrimental effect on the resin flow during the preform consolidation. Phillips et al demonstrated for instance that the impregnation of a carbon reinforcement with PEEK films is strongly reduced after a heat treatment of a few seconds at 400 C. 34 Therefore, the probability that the properties of PAEK matrices are modified during the fabrication of composite preforms is not negligible.…”
Section: Introductionmentioning
confidence: 99%